Metode SITUTE Berbasis Kabel STEM untuk Melatih Keterampilan dan Kreativitas Siswa di Masa Pandemi - Lufia Krismiyanti (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2023)
This study aims to describe the implementation of the STEM learning process and the achievement of STEM learning through the SITUTE method to train the skills and creativity of class IX A students of State Junior High School 1 Brebes semester 2 of the 2020/2021 academic year. This research was conducted on class IX A students at State Junior High School 1 Brebes Semester 1 for the 2020/2021 academic year. The research data is in the form of scores of students’ skills and creativity. Data collection techniques in the form of tests and non-tes. Data analysis was carried out qualitatively and quantitatively. The results of the study show that STEM learning through the SITUTE method can be implemented properly according to the learning implementation plan (RPP). Students’ skills in STEM learning through the SITUTE method are trained on aspects of identity, tools and materials, work methods, product appearance, packaging appearance with an average achievement of 81.4%. Students’ creativity is trained on aspects of new products, new procedures, originality, environmentally friendly, and promotional techniques with an average achievement of 69%. STEM learning through the SITUTE method can be used as an alternative in training students’ skills and creativity.